Pengaruh PowerPoint Interaktif terhadap Kemampuan Pencegahan Pelecehan Seksual di Taman Kanak-Kanak Islam Silaturahmi Kabupaten Padang Pariaman - Yulia, Rahmi; Pransiska, Rismareni (Lembaga Yasin AlSys, 2025)
Preventing sexual harassment among early childhood students remains a challenge at TK Islam Silaturahmi, Padang Pariaman Regency, necessitating effective learning methods to enhance children's ability to recognize and avoid such risks. This study aims to examine the effect of using interactive PowerPoint compared to animated video media on children's ability to prevent sexual harassment. A quasi-experimental method was used, involving two purposively selected classes: Class B1 as the experimental group and Class B2 as the control group, each consisting of 10 children. Research instruments included performance tests, observation sheets, and field notes, all of which were tested for validity and reliability using SPSS version 30. Data analysis included normality tests, homogeneity tests, independent t-tests, and effect size calculation. The results showed that the average score for sexual harassment prevention ability was higher in the experimental group (17.1) than in the control group (16.1). The homogeneity test indicated that the data were homogeneous (sig 0.172 > 0.05), and the t-test showed no statistically significant difference (sig 0.084 > 0.05). However, an effect size of 0.82 indicated a large practical effect. These findings demonstrate that interactive PowerPoint has a significant practical impact and is effective in enhancing early childhood students’ ability to prevent sexual harassment in kindergarten educational settings.